Characteristics of Riehl melanosis in an ethnic Asian population: A comparative study according to age, sex, and hair dye use - Myoung Eun Choi; Youngkyoung Lim; Woo Jin Lee; Chong Hyun Won; Mi Woo Lee; Sung Eun Chang (Wiley, 2022)
Abstract Background Riehl melanosis, characterized by diffuse brown to grey hyperpigmentation of the face and neck, affects middle‐aged women with dark skin phototypes. Riehl melanosis prevalence has increased in Korea, and a relationship with henna hair dye has been suspected. In this study, we aimed to evaluate clinical features and patch test results of Riehl melanosis patients and analyse them according to age, sex, and hair dye use. Methods We identified patients showing clinical and histopathological manifestations consistent with Riehl melanosis between January 2009 and December 2019 in our medical centre. Results Of 154 patients, 76.5% had positive patch‐test results, and the most common sensitizing agents were nickel, cobalt, and benzyl salicylate. Patients ≥50 years old were more likely to have spotty hyperpigmentation and less likely to have diffuse patterns, while lesions in the younger‐aged group were more commonly accompanied by erythema. Preceding erythema was found more often in female patients. Hair dye usage was more likely to be associated with aggravation of symptoms in females. Patients who developed Riehl melanosis after hair‐dye use more frequently had lesions on the forehead and were diagnosed an average of 14.1 months earlier as compared with other patients. Short disease duration, aggravation by hair dye (except henna), laser therapy, and longer follow‐up periods were related to good treatment responses. Conclusions Detailed history taking regarding disease duration and aggravating factors as well as the length of the period of laser therapy can be important for the management of Riehl melanosis patients.